P-resonant control for the neutral point of three phase inverter - Omar Aashour, Omar Ali (2014)
In this project, a Proportional resonant (PR) current controller is proposed to maintain a balanced neutral point for a three-phase four wire inverter, which can be used in microgrid applications. The neutral-point circuit consists of a conventional neutral leg and a split DC link. The neutral point is balanced with respect to the two DC source terminals (as required, in neutral-point clamped three-level converters) even when the neutral current is large so that the inverter can be connected to an unbalanced load. The controller, designed by using the Proportional resonant control techniques, which attain eliminate for the current flowing through the split capacitors. This leads to very small variation of the neutral point from the mid-point of the DC source, in spite of the possibly large neutral current. The simulation of inverter circuit, neutral-point and P-resonant has been performed using MATLAB/SIMULINK software. The simulation results confirm the validity of the proposed method, which can be seen as a promising that ensure P-resonant control suitable for microgrid applications.